PENGARUH SUMBER INFORMASI TERHADAP KEPUTUSAN NASABAH MENGGUNAKAN TABUNGAN BRITAMA - Novita Rosanti (AkMen JURNAL ILMIAH, 2016)
The study aims to determine the influence of resources on the customer's decision to use the savings Britama, and know the most dominant sources of information that influence the customer's decision. Data are obtained from the primary data with questioning techniques. Saving all customers of the population. Determination of the number of samples using the formula Slovin and obtained as many as 100 people Penyebarann ​​questionnaire using accidental sampling technique. The analytical method used is quantitative analysis with multiple linear regression and test of data using Validity Test, Test Reliability Test, T (t-test), Test Asumsik Classical and Simultaneous Testing. The results showed that the source of positive influence is not significant personal, commercial sources and no significant negative effect, public resources and significant positive effect, as well as the source of the experimental positive and significant impact. Source Experimental become the most dominant variable in influencing the customer's decision to use the savings Britama.